Analisis Pengendalian Persediaan Bahan Baku dengan menggunakan Metode Material Requirement Planning pada Batik Putri Nderbolo Masaran Sragen - Nur Viana Sukma Melati; Sunarso Sunarso (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Every company must always strive to be able to produce effectively and efficiently by utilizing production factors to produce quality products of course and the production process is the core activity of a company. The company must have a management system that will make the company continue to improve and be better. The company is expected to operate in the long term. Companies whose main activities are producing goods must pay attention to things that support the smooth running of their production. Smooth production must be supported by the availability of raw materials which are one of the triggers for increased costs. A system that can be used to overcome a problem related to raw material inventory planning is the Material Requirement Planning (MRP) method. The main purpose of MRP is to design a system that can produce information to take appropriate action related to purchasing or the production process. In addition, the author wants to know the effect of MRP on raw material inventory planning for Batik Putri Nderbolo Masaran Sragen. Based on the results of the research that has been conducted, the researcher concluded that the most efficient method applied in Batik Putri Nderbolo Masaran Sragen is Lot For Lor (LFL) and Economic Order Quantity (EOQ). From the results of the study, the total cost of the company's raw material inventory was Rp 9,102,274, which is greater than the Material Requirement Planning (MRP) method with the Lot For Lor (LFL) technique of Rp 1,061,544, Economic Order Quantity (EOQ) of Rp 7,167,522, and Period Order Quantity (POQ) of Rp 1,061,544.